Kuduro, rap and resistance: Politics of music and activism in ‘new’ hegemonic Angola - Czegledi, Alexandra (Department of Political Studies, 2019)
Keywords: kuduro, rap, music, diasporic, resistance, neoliberalism, seductive power, necropower, frozen citizenship, electronic capitalism, visibility, human rights I introduce kuduro music as a vantage point to uncover the political landscape of Angola where critical voices do not emerge with ease. I argue that kuduro, the globally known and disseminated genre of dance music, has been hijacked by the dos Santos government’s populist narrative so that it has become an ideological audio-visual narrative for ‘new’ Angola. Co-option is a socio-economic practice in new, independent Angola, but also political in the sense that it brings Angolans closer to the ruling elite’s economic power. The redistribution of wealth what Kalyan Sanyal (2007) coined as reversal of primitive accumulation is a useful concept here, but it falls short of fully explaining practices of patronage. Thus, I suggest seductive power as an extended concept, in order to understand co-option as both an economic and a cultural practice. In contrast to the kuduro scene, rap and hip-hop music have remained part of underground and DIY culture in Angola. This quasi-marginal position has allowed some musicians’ artistic practice to emerge as critical voices. In this mini-dissertation, I examine Ikonoklasta and MCK’s music because they are among the most represented musicians and activists by online media. New modes of civil resistance are often attached to Ikonoklasta’s name and songs. However, the recently emerged revolutionary’s movement cannot be fully identified with the Angolan rap scene (Martin 2015). In this sense, through Ikonoklasta’s activism and music production, along with MCK’s music, I show the extent to which the Angolan government keeps a certain culture of fear alive through necropolitics which was coined by Achille Mbembe (2003). This politics of death, and consequently, that of fear jointly produce what I call ‘frozen citizenship’. Before the revolutionary youth were arrested, Ikonoklasta and MCK collaborated with Batida, the Lisbon-based kuduro musician. Moreover, following the detention of musicians, local journalists and academics in Luanda, Batida began to use its global music network and platform to tell stories about the Angolan revolutionary movement. Repurposing his world music shows and DJ sets, Batida has enabled the dissemination of local counter-narratives within transnational NGOs’ circle. Pedro Coquenão aka Batida have organised demonstrations by utilising the global infrastructure and intellectual labour of Amnesty International. To elaborate on the transnational NGO’s role, I draw on critical human rights scholarship which consider human rights language as a global hegemonic framework engaging with injustices in a depoliticizing manner. Moving away from this theoretical preconceptions, I briefly discuss the extent to which transnational NGOs such as Amnesty International, paradoxically constrains and enables local activism at the same time. Although human rights organizations seem to have little power to put pressure on the Angolan government, they have the financial and infrastructural means to disseminate images, music and stories of local activists. I argue that this visibility provides global attention and certain protection to the high-profile activists targeted by the dos Santos regime. This medium falls in the trap of global witness fever (Kurasawa 2009) which offers an escape from ‘frozen citizenship’ through positive activist practice and a politics of hope (Baridotti 2010).